Covid-19 in Islamic perspective: overview of its impacts on students in the Faculty of Islamic Studies (FPI), National University of Malaysia (UKM) - Ahmad Yunus Mohd Noor; Asmilyia Mohd Mokhtar (Penerbit Universiti Kebangsaan Malaysia, 2023)
Covid-19 pandemic have been directly and indirectly given several impacts on the universities in Malaysia. The Ministry of Higher Education has announced that online learning will be replacing the face-to-face learning, to ensure education continuity. This study attempts to examine the impacts of Covid-19 on the daily life of students, and to observe the ways taken by students in the Faculty of Islamic Studies, National University of Malaysia (UKM) to overcome the effects of Covid-19. This research uses an online survey method and it has been conducted toward 30 students by using Google Forms through WhatsApp and Telegram. The findings show that majority of 30 students agree that the Covid-19 influences and impacts towards their daily life because they no longer eager to learn, miss a lot in their learning, and most of them had difficulty to find reference materials. Besides, most students also feel depress when the Covid-19 happen, their academic performance declining, and they have to bear the cost of loss when they have to return to their residence in regards with the government’s hasty decision for not to allow them to return to the campus. In addition, the research found that majority of students spend their times with family to overcome the effects of Covid-19. Data collection shows that they also think positively and prepare a study schedule. Hence, they could spend time to do revision and complete assignments.